Phytochemical potential, antiradical and antimicrobial activity of crude extracts of Caesalpinia benthamiana roots used for oral hygiene in Benin republic - Olayé, Théophile; Tchobo, Fidèle Paul; Chabi, Nicodème Worou (My University, 2018)
Triclosan Oral hygiene is a determining factor in the prevention of oral diseases. In other to meet this challenge, rural populations in several developing countries including those of Benin Republic use chewing stick, whose activity are yet to be elucidated. The objective of this present work was to analyse the phytochemical, the antioxidant and antimicrobial activities of the root of Caesalpinia benthamiana, a chewing stick used in Benin Republic for oral hygiene using standard techniques described in the literature. The ethanolic extract exhibited a good ability to inhibit the DPPH radical and also to reduce ferric Fe3+ ion to ferrous Fe2+ ion and this could explain their rich content in phenolic compounds. The ethanolic extract also exhibited a good antimicrobial activity against Proteus mirabilis with MIC value of 6,250 mg/mL.
Keywords: Phytochemical; antimicrobial; antioxidant; chewing stick; oral hygiene